PENGARUH KOMEPENSASI FINANSIAL, LINGKUNGAN KERJA NON FISIK DAN STRES KERJA TERHADAP KEPUASAN KERJA (STUDI KASUS PADA PT PLN (Persero) Up3 Bima) - Rais Manyusuf Riadin Manyusuf Riadin; Jaenab Jaenab (Jurnal Inovasi Penelitian, 2022)
This study aims to determine how the level of financial compensation, non-physical work environment and stress on job satisfaction (a case study at PT. PLN (Persero) Up3 Bima. The instrument in this study used a questionnaire with a Likert scale. The population in this study was to find 45 people employees at PT. PLN (Persero) Up3 Bima with saturated sampling technique. Data collection techniques using observation, interviews, questionnaires and documentation. Data analysis techniques using validity tests, reliability tests, classical assumption tests, f tests and t tests, using assistance spss version 22 for windows. Based on the results of the t test on financial compensation for the non-physical work environment and job stress on job satisfaction (a case study at PT. PLN (Persero) Up3 Bima. It is said to meet the criteria or good because it is more than 75%, where financial compensation,non-physical work environment and work stress on job satisfaction (case study at PT.PL N (Persero) Up3 Bim a is in accordance with the wishes expected by the company with a t-count level of financial compensation t-table (2.161≥ 2.018), stating that Ho is rejected and Ha is accepted with a value of 0.037 0.05 meaning significant. Non-physical work environment t-count value Non-physical work environment t-table (-3.364≥ 2.018), states that Ho is rejected and Ha is accepted with a significant value of 0.002 0.05 means significant. Work stress t-count work stress t-table (3.512≥ 2.018), stating that Ho is rejected and Ha is accepted with a significant value of 0.001 0.05, which means significant.